Assessment of non-tumor liver parenchyma damage in advanced gastric cancer treatment with transarterial infusion chemotherapy: a study using imaging and hepatic injury indicators - Jing, Yifan; Jing, Jian; Sun, Xiaokang; Jin, Yong; Bai, Xuming (Frontiers in Oncology, 2025)
IntroductionThis study aimed to evaluate non-tumor liver parenchymal injury in advanced gastric cancer patients undergoing transarterial infusion chemotherapy (TAI) using imaging parameters and liver injury biomarkers, providing objective evidence for early detection of drug-induced liver injury.MethodsA retrospective analysis was conducted on 52 advanced gastric cancer patients who received TAI at our center from July 2015 to July 2023. Abdominal CT images and laboratory data were collected before and after treatment. Imaging postprocessing software was used to measure the liver-to-spleen (L/S) attenuation ratio and spleen volume. Liver fibrosis indices (APRI, FIB-4) and liver function scores (Child-Pugh, ALBI) were calculated. Statistical analysis included Wilcoxon rank-sum test and paired t-test for pre- and post-treatment comparisons.ResultsPatients received an average of 2.80 TAI cycles over 8.3 weeks. Post-treatment, 76.92% (40/52) showed a significant reduction in L/S attenuation ratio (1.23 ± 0.13 vs. 1.12 ± 0.1, P < 0.01), and 73.1% (38/52) exhibited increased spleen volume (151,219.33 mm³ vs. 202, 171.32 mm³, P < 0.01). Liver fibrosis indices significantly increased: APRI (0.19 ± 0.15 vs. 0.37 ± 0.27) and FIB-4 (1.29 ± 0.88 vs. 2.24 ± 1.38) (P < 0.01). No significant changes were observed in ALBI (-2.7 ± 0.41 vs. -2.58 ± 0.43) or Child-Pugh scores (5.31 ± 0.47 vs. 5.38 ± 0.64) (P > 0.05).DiscussionTransarterial infusion chemotherapy for advanced gastric cancer results in short-term damage to the non-tumor liver parenchyma, with imaging findings showing hepatic steatosis (reduction in L/S ratio) and splenomegaly. Serum markers suggest progression of hepatic fibrosis, consistent with the pathological features of hepatic sinusoidal obstruction syndrome. The combination of CT imaging and APRI/FIB-4 provides a sensitive method for detecting subclinical liver injury, reflecting pathological changes earlier than traditional liver function scores.